Optical Fiber Sensor Experimental Research Based on the Theory of Bending Loss Applied to Monitoring Differential Settlement at the Earth-Rock Junction. (17th June 2015) - Qiu, Jianchun; Zheng, Dongjian; Zhu, Kai; Fang, Bin; Cheng, Lin
Abstract : Considering the differential settlement in the junction between the structure perpendicular to the dike and the body and foundation of dike (called the earth-rock junction in this paper) during runtime, an experimental investigation of optical fiber sensor monitoring was conducted. Based on the sensing mechanism of single-mode optical fiber bending loss, the experiment focused on the influence of the bending radius of an optical fiber on the bending loss. In view of the characteristics of the differential settlement in the earth-rock junction, we designed a butterfly-type optical fiber sensor and composite optical fiber sensor for monitoring device in monitoring the differential settlement to enlarge the monitoring range and improve the sensibility of optical fiber sensor. Based on the research on the working principle and bending properties of the composite optical fiber monitoring device, we conducted experiments on the bending of the composite optical fiber sensor monitoring device and the use of the device for monitoring the differential settlement. These experiments verified the feasibility of the composite optical fiber sensor monitoring device at monitoring the differential settlement in the earth-rock junction.